Evaluation of the effect of the treatment with diluted sulfuric acid of the lignocellulosic material of pineapple waste, to produce sugars as a substrate in the aqueous phase reforming reaction (APR) - Brenes, Mauricio Ulate (2021)
The main objective of the study was to evaluate the rate of production of hydrogen through aqueous phase reforming (APR), using the product of the hydrolysis of lignocellulosic material of pineapple’s straw. The characterization of the pineapple’s straw (MD2) was carried out. Then, a fractional factorial design was carried out to study the effect of diluted sulfuric acid concentration (1 %m/m y 3%m/m), temperature (100 °C y 140 °C) and solid-liquid ratio (1:6 g/mL y 1:9 g/mL). For the aqueous phase reforming (APR), it was used 5 % mass of catalyst based on the glucose mass in the hydrolysis product. The catalyst used was impregnated nickel in commercial alumina. The temperature (473.15 K) and the time of reaction (2 h) were set, and the nickel mass in the catalyst varied in three levels (5%, 20% y 35 %). It was found that the rate of hydrogen production was 221 mmol gcat-1 h-1, According to the statistical design, it was observed that 35 % of nickel is significant.